Influence of hydrogen and oxygen on the structure and properties of sputtered magnesium zirconium oxynitride thin films. Issue 18 (4th May 2020) - Kim, Jekyung; Bauers, Sage R.; Khan, Imran S.; Perkins, John; Park, Bo-In; Talley, Kevin R.; Kim, Daehan; Zakutayev, Andriy; Shin, Byungha
Abstract : Nitride materials with mixed ionic and covalent bonding character and resulting good charge transport properties are attractive for optoelectronic devices. Abstract : Nitride materials with mixed ionic and covalent bonding character and resulting good charge transport properties are attractive for optoelectronic devices. Recently, Mg-based ternary nitride materials were found to have large dielectric constants and high absorption coefficients with bandgaps appropriate for photovoltaic applications. However, their degenerate carrier concentrations still hinder their possible applications in solar cells and related optoelectronic devices. Therefore, further understanding and engineering of the parameters controlling the material properties of these ternary nitrides is highly desirable. Here we report that the structural, optical and electrical properties of magnesium zirconium oxynitride (MZNO) thin films synthesized by combinatorial sputtering with a wide range of cation compositions can be affected by incorporation of oxygen and hydrogen. Excess oxygen improved the crystallinity of MZNO thin films whereas hydrogen attracted oxygen and formed Mg-rich oxide layers at the grain boundaries which in turn reduced the conductivity. On the other hand, optical properties are more sensitive to the composition – both cation and anion ratios – rather than the presence of hydrogen. Compared to cation-stoichiometric MZNO (10 19 –10 20 cm −3 ), substantial reduction of carrier concentration down to ∼10 14 cm −3 was achieved under Mg-rich conditions by supplying hydrogen during growth. Photoluminescence measurements showed that the films prepared with hydrogen were optoelectronically active. Overall, this study demonstrates that the material properties of MZN thin films can be significantly influenced by incorporation of oxygen and hydrogen.